Pirates of the Caribbean. Dead men tell no tales [videorecording (Blu-ray + DVD)] - Depp, Johnny; Bardem, Javier, 1969-; Thwaites, Brenton, 1989-; Scodelario, Kaya, 1992-; McNally, Kevin; Wenham, David, 1965-; Graham, Stephen, 1973-; Rush, Geoffrey, 1951-; Barnett, Angus; Klebba, Martin; Brown, Adam, 1980-; New, Giles (Disney Blu-ray., 2017)
Captain Jack Sparrow finds the winds of ill-fortune blowing even more strongly when deadly ghost pirates led by his old nemesis, the terrifying Captain Salazar, escape from the Devil's Triangle, determined to kill every pirate at sea. His only hope of survival lies in seeking out the legendary Trident of Poseidon, a powerful artifact that bestows upon its possessor total control over the seas.